Deadly promises (New York Pocket Star Books, 2010)
The heroes of the Bureau of American Defense, Black Ops, Inc., and U.S. Navy SEALs are cool under pressure, steamy under the sheets, and lethal when handling any mission.
Just bad enough / Sherrilyn Kenyon and Dianna Love -- Leave no trace / Cindy Gerard -- Unstoppable / Laura Griffin.
Keywords: United States. -- Navy. -- SEALs -- Fiction; Love stories; Suspense fiction